A importância da ludicidade na educação infantil - MONTEIRO, Carmem Lúcia dos Santos Sousa (2024)
The present research has as its theme: The importance of the playful in Infant Education and aims to question and think of solutions for effective learning, faced with the following problem: What is the capacity of the child to develop the skills of the child in Early Childhood Education? The purpose of the present work is to elaborate the importance of the playful in the teaching-learning process, seeking to understand the relevance of playing as a subsidy in the construction of development, learning in the educational process of the child. The work was developed through a research based on the foundations of authors such as VYGOTSKY (2003), LUCKESI (2005), KISHIMOTO (1997), SANTOS (1997), NEGRINE (1994), Cardoso school. Therefore we try to identify that the use of playful allied pedagogic activities can transform learning into a pleasurable action that produces positive results.